Age-dependent increases of calcium and phosphorus in human epiglottal cartilage - Cho Azuma (2018)
To elucidate compositional changes of the elastic cartilage with aging, the authors investigated age-related changes of elements in the epiglottal cartilages by inductively coupled plasma-atomic emission spectrometry. After the ordinary dissection by medical students at Chiang Mai University was finished, the epiglottises were resected from the subjects. The epiglottal cartilages were isolated and the element contents were determined. The subjects consisted of 11 men and 14 women, ranging in age from 39 to 92 yr old. It was found that although the extent of accumulation of calcium and phosphorus was slight, calcium and phosphorus increased progressively in the epiglottal cartilages with aging. In contrast, sulfur, magnesium, zinc, iron, and sodium did not change significantly in them. Regarding the relationships among elements, it was found that there were significant correlations among calcium, phosphorus, magnesium, and sodium in the epiglottal cartilages, with one exception between calcium and sodium contents. In comparison between men and women, no significant differences were found in the predominant elements such as calcium, sulfur, and phosphorus in the epiglottal cartilages. © Copyright 2005 by Humana Press Inc.